Interaksi Simbolik Pengajar dan Siswa di Komunitas Matahari Kecil - Tasya Aulia Maghfira; Adi Bayu Mahadian (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2018)
SMP Terbuka Gading Regency is a free school founded by the Matahari Kecil community to alleviate the burden of underprivileged students. The purpose of this study was to figure out the symbols and the meaning negotiation in the interaction in forming the self-concept of teachers and students. The theory underlying this research was the symbolic interaction according to George Herbert Mead. This study used in-depth interviews and observations on four students, teachers, and supporting informants for each who were selected with purposive sampling techniques. The result showed that the interaction of teachers and students was built through formal and informal interpersonal relationship. There was an exchange of verbal and nonverbal symbols in shaping the same meaning in the interaction. The meaning formed in the interaction process affected the self-concept of the teachers and students. As a result, there was a change in self-concept of students and teachers during the interaction. The self-concept was inseparable from the role of mind, self, and society of the teachers and students.